Pengaruh Aktivasi Kimia Arang Tanaman Eceng Gondok (eichhornia crassipes) Terhadap Adsorpsi Logam Timbal (Pb) - Sangkota, Vivi Dia A.; Supriadi, Supriadi; Said, Irwan (Jurnal Akademika Kimia, 2017)
This study aimed to determine the optimum pH and the optimum weight of charcoal and activated charcoal from water hyacinth in adsorbing the lead (Pb) metals. Determination of adsorbed metal content in the charcoal and the activated charcoal was measured using a spectrophotometer spectrodirect. Activated water hyacinth charcoal was prepared by carbonization in a furnace at a temperature of 300 oC in low oxygen levels. Then the carbon was activated by adding ZnCl2 10%, soaked for 24 hours, filtered and placed in the oven at a temperature of 105 0C for 1 hour. The optimum pH was determined by mixing Pb2+ with water hyacinth (eichhornia crassipes) charcoal at various pH of 3-8. The results indicated the optimum pH of charcoal and activated charcoal to adsorb metals was 5 with the percentages of lead absorbed were 90.34% and 98.67%, respectively, while the weight of charcoal varied by 25, 50, 75, 100 and 125 mg, the optimum weight of activated charcoal was 100 mg with lead absorbed by 98.44%. The results showed that the water hyacinth charcoal and activated charcoal performed excellent ability to adsorb lead metal.